A Concept of the Correlation Between Pitta and Agni in Ayurveda (AYUSHDHARA, 2023)
One of the first healthcare systems to emerge on the Indian Subcontinent is Ayurveda. The fundamentals of Ayurvedic physiology are represented by the Panchbhautika Vikara which comprises of the three Doshas Vata, Pitta and Kapha, seven Dhatus and three Mala. The most significant biological component in charge of preserving homeostasis is the Dosha. Agni is a constant force that affects digestion and various hormone, enzyme and coenzyme functions. It is essential to the process of transformation and digestion. It is well known that the body undergoes numerous processes of transformation multiple times every second. Agni is one of the ten factors which are required to be examined before initiating the treatment of patients. According to Ayurveda, the condition of the Agni impacts all stages of health or sickness. As Pitta is accountable for digestion, metabolism, all biochemical and enzymatic reactions, heat production, hemopoiesis, visual functions, higher mental faculties, its functions can be undertaken through the body's endocrine system. This Article aims to explore each of these components of Pitta Dosha and Agni, as well as their interrelation and how they interact in modern sciences. According to Aacharya Sushruta, Pitta and Agni are one and the same. The fire element or Agni, resides in the Pitta region of the body. Pitta and fire both serve comparable purposes.